Investigation on the effectiveness of a new hoof care product to sustainably reduce and prevent digital dermatitis in dairy cow herds - K. Grimm; A. Fiedler; C. Kröger (Journal of Dairy Science)
ABSTRACT: The regular application of hoof care and cleaning products is an important part of protocols designed to reduce burden of disease caused by the ubiquitous and multifactorial hoof disease digital dermatitis (DD) in dairy cows. Commonly used hoof care products such as formalin or copper sulfate applied through foot baths or by spraying hindfeet are often irritant to the skin as well as harmful to the environment or human health, and scientifically proven evidence of their efficacy is scarce. Thus, in a clinical controlled trial, we investigated whether the use of a hoof care product based on a mix of iron complex salts, zinc salts, and aluminum designed to reduce bacterial load on the skin and to support the natural skin barrier, was able to sustainably reduce disease severity and prevent new cases in 132 cows in 2 dairy herds (n1 = 72, n2 = 60) in Germany. From Dec 2021 to Dec 2022 only one predefined hind foot of every cow was washed and sprayed with the product twice a week (treatment group), the other hind foot was only washed (control group). Heifers joining the herd were sprayed for at least 4 wk beforehand according to the same treatment and control regimen. During the trial, hooves were numerically scored for DD lesions on a monthly basis using a disease severity score (A): from 0 = no lesion, up to 60 = ulcerative lesion ≥2.5 cm and categorically with 3 categories (B): none, nonactive, and active. Results A: Mean area under the curve of the numerical score that summarizes development over time was substantially and significantly smaller in the treatment group. Results B: Two-step regression analysis for the outcome category at evaluation day (with exclusion of the first baseline evaluation) showed that during the trial, compared with the treatment group, odds of having a lesion rather than none was 4 times higher in the control group and the odds of having an active lesion compared with an inactive one were almost 6 times higher in the control group. Additionally, spraying had a significant preventive effect for the feet of heifers (n = 17) introduced to the herd during the trial on farm 1: Only one active lesion occurred in the treatment group with numerous active lesions observed in the control group and mean area under the curve of the numerical score over time was significantly lower in the treatment group, too. No active lesions occurred in the heifers of farm 2 (n = 12) in either of the study groups. The iron, zinc, and aluminum-based product effectively reduced disease prevalence and disease severity during the 1-yr study period in the examined dairy herds, and data from heifers suggest that the application of the product to heifers 4 wk before entering a herd with controlled DD management measures has high potential for prevention of the disease.